O wykrzykniku w słowniku, czyli kilka uwag o artykułach wykrzykników języka rosyjskiego i polskiego w słownikach objaśniających - Malinowska, Iwona (Acta Polono-Ruthenica, 2018)
The author analyzed the exclamation entries in Russian and Polish dictionaries. The article aims to present various ways of the dictionary exclamation description exemplifying it by one primary (A! – a!) and one secondary (Боже! – Boże!) exclamations. The paper is to show the shortcomings and propose corrections in lexicographical description of exclamations. Due to the frequency of their use in speech and writing, the author also proposes to increase the number of exclamation entries in explanatory dictionaries. Compilation of a separate exclamation dictionary in both of the analyzed languages is worth considering.